Analisa Cost and Benefit atas Sustainability Reporting - Lusy Lusy; Vincentia Devina (STIE PGRI Dewantara Jombang, 2021)
This research tootk the topik of Sustainability Reporting, to creat a Triple Bottom Line Implementation. The target of this research is to raise awareness of the company, to be responsible for economic, social, and environmental aspects, including reducing production waste, and reprocessing it into waste that is safe for the environment. The object of this research is BUMN in the mining sector. The method used in this research is descriptive qualitative, by taking secondary data from the Indonesia Stock Exchange. The data obtained are analyzed for Cost and Benefit, so that we know the benefits of environmental care, known as Corporate Social Responsibility (CSR). This research shows that the cost and benefits of the CSR program are already running effectively. The increase in costs increases public confidence, especially in preserving the environment and improving the standard of living of the community, through an educational program financed by the state-owned mining company.